DEVELOPING ENTERPRISE ARCHITECTURE USING TOGAF 9.1 FOR IT MASTER PLAN IN THE GRADUATE PROGRAM OF INSTITUTE OF INFORMATICS AND BUSINESS DARMAJAYA - Sutedi Sutedi; Nirmala Handayani (Prosiding International conference on Information Technology and Business (ICITB), 2020)
The graduate program of Institute of Informatics and Business (IIB) Darmajaya was established in September 2009. This graduate program had two programs, e.g., Master of Management (MM) Program and Master of Informatics Engineering (MTI) Program. The implementation of the educational services in this graduate program was carried out through computer devices and had not used a special system. The data of the educational services had been stored into personal computers (PCs) and the the back-up data were managed into offline medium through external hard disks. The problem statement of this study was that there was a high risk of the data damage / loss so that the act of violating the acceptable standards of the educational standards emerged. The importance of excellent service and good data security of the graduate proogram of IIB Darmajaya created the ideal IT support. The objective of this study was conducting the IT Master Plan to support the implementation of all educational services of the graduate program of IIB Darmajaya. This IT Master Plan was carried out through an enterprise scale. The Togaf 9.1 was a framework for enterprise architecture development that provided a comprehensive approach to designing, planning, implementing, and managing the enterprise information architecture. TOGAF 9.1 was assessed through the business needs of the graduate program of IIB Darmajaya. Therefore, the graduate program of IIB Darmajaya had a master plan for IT development used as a guide for implementing IT at the institution level. The targeted IT development plan in accordance with the users' needs and requirements also increased the effectiveness of IT implementation in order to improve the service quality and guarantee the data security at IIB Darmajaya.Keywords: NodeMcu TOGAF 9.1, Postgraduate, Enterprise